Long-term analysis of ionospheric response during geomagnetic storms in mid, low and equatorial latitudes - Matamba, Tshimangadzo Merline (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2018)
Understanding changes in the ionosphere is important for High Frequency (HF) communications and navigation systems. Ionospheric storms are the disturbances in the Earth's upper atmosphere due to solar activities such as Coronal Mass Ejections (CMEs), Corotating interaction Regions (CIRs) and solar flares. This thesis reports for the first time on an investigation of ionospheric response to great geomagnetic storms (Disturbance storm time, Dst ≤ −350 nT) that occurred during solar cycle 23. The storm periods analysed were 29 March - 02 April 2001, 27 - 31 October 2003, 18 - 23 November 2003 and 06 - 11 November 2004. Global Navigation Satellite System (GNSS), Total Electron Content (TEC) and ionosonde critical frequency of F2 layer (foF2) data over northern hemisphere (European sector) and southern hemisphere (African sector) mid-latitudes were used to study the ionospheric responses within 15E° - 40°E longitude and ±31°- ±46° geomagnetic latitude. Mid-latitude regions within the same longitude sector in both hemispheres were selected in order to assess the contribution of the low latitude changes especially the expansion of Equatorial Ionization Anomaly (EIA) also known as the dayside ionospheric super-fountain effect during these storms. In all storm periods, both negative and positive ionospheric responses were observed in both hemispheres. Negative ionospheric responses were mainly due to changes in neutral composition, while the expansion of the EIA led to pronounced positive ionospheric storm effect at mid-latitudes for some storm periods. In other cases (e.g 29 October 2003), Prompt Penetration Electric Fields (PPEF), EIA expansion and large scale Traveling Ionospheric Disturbances (TIDs) were found to be present during the positive storm effect at mid-latitudes in both hemispheres. An increase in TEC on the 28 October 2003 was because of the large solar flare with previously determined intensity of X45± 5. A further report on statistical analysis of ionospheric storm effects due to Corotating Interaction Region (CIR)- and Coronal Mass Ejection (CME)-driven storms was performed. The storm periods analyzed occurred during the period 2001 - 2015 which covers part of solar cycles 23 and 24. Dst≤ -30 nT and Kp≥ 3 indices were used to identify the storm periods considered. Ionospheric TEC derived from IGS stations that lie within 30°E - 40°E geographic longitude in mid, low and equatorial latitude over the African sector were used. The statistical analysis of ionospheric storm effects were compared over mid, low and equatorial latitudes in the African sector for the first time. Positive ionospheric storm effects were more prevalent during CME-driven and CIR-driven over all stations considered in this study. Negative ionospheric storm effects occurred only during CME-driven storms over mid-latitude stations and were more prevalent in summer. The other interesting finding is that for the stations considered over mid-, low, and equatorial latitudes, negative-positive ionospheric responses were only observed over low and equatorial latitudes. A significant number of cases where the electron density changes remained within the background variability during storm conditions were observed over the low latitude stations compared to other latitude regions.
Keywords: Ionospheric storms; Coronal mass ejections; Corotating interaction regions; Solar flares; Global Positioning System; Ionospheric critical frequencies; Equatorial Ionization Anomaly (EIA)